TINJAUAN LITERATUR : REKOMENDASI, MEKANISME AKSI, RISIKO, DAN PENDEKATAN EXERCISE INOVATIF PADA PASIEN GAGAL JANTUNG KRONIS - Hidayat, Adil (Yayasan Menawan Cerdas Indonesia, 2025)
Heart failure (HF) is a complex clinical syndrome that can occur due to various structural or functional cardiac disorders, leading to impaired ventricular function in terms of blood filling or ejection. This condition represents the advanced stage of cardiovascular diseases. HF is associated with a decrease in the proliferation rate of cardiac muscle cells and the occurrence of cardiomyocyte apoptosis (cell death). The progressive pathological process of cardiomyocyte apoptosis is linked to the age-related decline in cardiomyocyte renewal, resulting in the accumulation of intracellular waste products. Consequently, this further contributes to cardiomyocyte apoptosis, leading to increased metabolic demand and continued cardiac dysfunction. As is known, this condition is irreversible, and currently, no medical interventions can cure HF. However, individuals with chronic heart failure have several strategies and options available to actively manage their condition. Engaging in physical activity is considered one of the most effective non-pharmacological approaches. Therefore, this review presents an extensive and thorough examination of the exercise guidelines recommended for individuals with chronic heart failure. It provides a comprehensive analysis of the effects of exercise on heart function, along with explanations of the underlying mechanisms. Additionally, the review briefly discusses the potential risks associated with exercise in individuals with heart failure and explores innovative exercise approaches that can improve the condition for HF patients.